2004
DOI: 10.1023/b:nere.0000013737.17288.ce
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Participation of Sodium Channels on the Rise in Na+Induced by 4-Aminopyridine (4-AP) in Synaptosomes

Abstract: The participation of voltage-sensitive Na+ channels (VSSC) on the changes on internal (i) Na+, K+, Ca2+, and on DA, Glu, and GABA release caused by different concentrations of 4-AP was investigated in striatum synaptosomes. TTX, which abolished the increase in Na(i) (as determined with SBFI), induced by 0.1 mM 4-AP only inhibited by 30% the rise in Na(i) induced by 1 mM 4-AP. One millimolar 4-AP markedly decreased the fluorescence of the K+ indicator dye PBFI but 0.1 mM 4-AP did not. Like 1 mM 4-AP, ouabain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
1
24
0
1
Order By: Relevance
“…[K ϩ ] i was measured using PBFI fluorescence as described previously (28). In brief, potassium-binding benzofuran isophtalate acetomethylester was added to the cell suspension (10 M) and the cells were loaded for 1 h at 37°C.…”
Section: Measurement Of [Kmentioning
confidence: 99%
See 1 more Smart Citation
“…[K ϩ ] i was measured using PBFI fluorescence as described previously (28). In brief, potassium-binding benzofuran isophtalate acetomethylester was added to the cell suspension (10 M) and the cells were loaded for 1 h at 37°C.…”
Section: Measurement Of [Kmentioning
confidence: 99%
“…These data suggest that the inhibitory mechanisms in mIL-1␤ release by LPC and SPC on P2X7R-mediated response may not be related to K ϩ efflux. To further assess the effect of LPC and SPC on [K ϩ ] i , the change in [K ϩ ] i was monitored using PBFI fluorescence (28). We observed that 5 mM ATP induced a sustained decrease in the …”
Section: Lpc and Spc Do Not Inhibit Nigericin-induced Mil-1␤ Release mentioning
confidence: 99%
“…The involvement of K + channels in the mode of action of 4-aminopyridine at the presynaptic brain level, first suggested by the changes on 86 Rb + fluxes in brain nerve endings (Sitges et al, 1986), was confirmed later using the K + selective indicator dye, PBFI (Galindo & Sitges 2004). In summary, in cerebral isolated nerve endings 4-aminopyridine increases Na + channels permeability (Galván and Sitges, 2004), Ca 2+ channels permeability (Tibbs et al, 1989;Heemskerk et al, 1991;Galván & Sitges, 2004;, and decreases K + channels permeability (Sitges et al, 1986;Galván & Sitges, 2004). Therefore, the changes that may occur in cerebral nerve endings under the excitatory conditions that t a k e p l a c e d u r i n g s e i z u r e s s e e m t o b e m o re closely resembled by 4-aminopyridine; although its mechanism of action is complicated.…”
mentioning
confidence: 77%
“…More recently, we also test the effects of antiepileptic drugs in the cerebral nerve endings in vitro using 4-aminopyridine as depolarizing strategy. Because 4-aminopyridine exposure may more closely mimic some of the changes that may take place in the epileptic tissue, since in cerebral nerve endings 4-aminopyridine besides increasing the permeability of Na + and Ca 2+ channels, also decreases the permeability of some K + channels, and by this mean arrests indirectly the Na + /K + ATPase (Galván & Sitges, 2004), making even more difficult the limitation of neuronal excitability. Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation